O teorema de Pitágoras no oitavo ano do ensino fundamental - Stegani, Ozilde Peter (2014)
In this paper we reflect on a group of eight lessons applied in the eighth year of elementary school. In these classes, we treat the Pythagorean Theorem, seeking to justify this outcome appropriate to the student s eighth grade elementary school mode. We were interested in seeking justifications with historical content, to rescue, to the extent possible, a part of the history of the Pythagorean Theorem. We take care to seek a mathematical justification for each procedure adopted to develop pedagogical activities. Throughout the text brushing been several suggestions for improving the finished product, though it kept almost entirely in Appendix 1. Also critical to our work interweave throughout the text, seeking both personal growth as offering the opportunity for a better match of the final product to whom this is of interest. At the end we suggest some current applications of the Pythagorean Theorem. Finished the job in the classroom involving the class with the game of dominoes, adapted to the content studied, trying to leave a better final impression on the students. We describe the construction of pedagogical object, the math worked during such construction and finally its application in the classroom. We make four appendices. In the first present the final product. In the second we seek to exemplify the student s work. In the third and fourth work building Pythagorean triangles.